2018
DOI: 10.1186/s40560-018-0277-9
|View full text |Cite|
|
Sign up to set email alerts
|

Use of diaphragm thickening fraction combined with rapid shallow breathing index for predicting success of weaning from mechanical ventilator in medical patients

Abstract: BackgroundWeaning failure is a crucial hindrance in critically ill patients. Rapid shallow breathing index (RSBI), a well-known weaning index, has some limitations in predicting weaning outcomes. A new weaning index using point-of-care ultrasound with diaphragmic thickening fraction (DTF) has potential benefits for improving weaning success. The aim of this study was to evaluate the efficacy of a combination of DTF and RSBI for predicting successful weaning compared to RSBI alone.MethodsThis prospective study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 32 publications
(42 reference statements)
5
49
0
3
Order By: Relevance
“…However, it has some limitations in predicting weaning outcomes [5]. Several previous studies have defined different sensitivities and specificities for RSBI less than 105 to predict weaning success which may lead to errors in predicting successful weaning [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has some limitations in predicting weaning outcomes [5]. Several previous studies have defined different sensitivities and specificities for RSBI less than 105 to predict weaning success which may lead to errors in predicting successful weaning [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Diaphragm SWE appears to have a strong potential for direct, noninvasive, and specific assessment of diaphragm effort. SMdi coupled with functional respiratory investigations may help to detect diaphragm dysfunction (25). Although feasibility of diaphragm SWE in the left zone of apposition (and other approaches) remain to be investigated, it might be particularly useful for detecting diaphragm hemi-paralysis.…”
mentioning
confidence: 99%
“…Another study done by Pirompanich and Romsaiyut concluded that DTF ≥ 26% combined with RSBI ≤ 105 increased the rate of successful weaning compared to RSBI alone. 17 Our study found that DTF of more than 40% was associated with successful weaning. Establishment of MV and further therapeutic interventions were done in patients with DTFS ≤ 25%.…”
Section: Resultsmentioning
confidence: 50%